Case Report: Aveir implantation in an 8.7-year-old, 25-kg pediatric patient with mitochondrial disease via internal jugular vein - Zhou, Xue; Xu, Xin; He, Shuang; Liu, Qian; Lu, Tiewei (Frontiers in Cardiovascular Medicine, 2025)
IntroductionMitochondrial disorders frequently precipitate progressive conduction system degeneration, with complete heart block representing a critical therapeutic challenge in pediatric populations, which ultimately requires permanent pacemaker implantation. However transjugular venous implantation of the Aveir leadless pacemaker in a pediatric patient with mitochondrial disease has not been previously reported.Methods and resultsAn 8.7-year-old, female patient (weight: 25 kg) with genetically confirmed mitochondrial disease presented with cardiac syncope secondary to the complete atrioventricular block. Comorbidities included insulin-dependent diabetes and pocket infection from a conventional permanent pacemaker implanted four months prior. Given her history of device-related complications and restricted venous access, a retrievable leadless pacemaker (Abbott Aveir) was successfully implanted via the internal jugular vein under fluoroscopic guidance without complication. Stability testing confirmed adequate fixation with pacing threshold of 1.0V@0.2 ms and impedance of 610Ω at one-month follow-up.ConclusionThe Aveir VR leadless pacemaker can be safely implanted via the internal jugular vein approach in pediatric patients with mitochondrial disease.